Managing extreme climate change risks through insurance - Botzen, W. J. Wouter (Cambridge : Cambridge University Press, 2013)
In recent years, the damage caused by natural disasters has increased worldwide; this trend will only continue with the impact of climate change. Despite this, the role for the most common mechanism for managing risk - insurance - has received little attention. This book considers the contribution that insurance arrangements can make to society's management of the risks of natural hazards in a changing climate. It also looks at the potential impacts of climate change on the insurance sector, and insurers' responses to climate change. The author combines theory with evidence from the rich experiences of the Netherlands together with examples from around the world. He recognises the role of the individual in preparing for disasters, as well as the difficulties individuals have in understanding and dealing with infrequent risks. Written in plain language, this book will appeal to researchers and policy-makers alike.
1. Climate change and natural disaster risk management -- 2. Climate change impacts on the insurance sector -- 3. Climate change and future costs of natural disasters -- 4. Climate change adaptation through insurance against flooding -- 5. Dealing with uncertainty in flood risk management -- 6. Damage mitigation measures at the household level and climate change adaptation -- 7. Insurance incentives for homeowners to invest in adaptation -- 8. Bounded rationality and demand for flood insurance -- 9. Individual perceptions of flood risk -- 10. Willingness-to-pay (WTP) for insurance against low-probability flood risks -- 11. Market shares of insurance against flood risk under climate change scenarios -- 12. Conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Risk management; Natural disasters; Climatic changes